Paired DNA/RNA testing uncovers a deep intronic PTEN pathogenic variant associated with clinical Cowden Syndrome: a case report - Hall, Michael J; Kim, Dong Won; Namjoshi, Devang; McSweeny, Michelle; Richardson, Marcy E; Marsh, Ashley PL; Hernandez, Felicia; Dedousis, Demitrios (Frontiers in Oncology, 2025)
Identification of a deep intronic PTEN pathogenic variant, which was not detected by standard DNA-targeted panel sequencing but was uncovered by targeted PTEN RNA sequencing using CaptureSeq technology, illustrates the added value of concurrent DNA and RNA analyses in risk assessment for PTEN Hamartoma Tumor Syndrome (PHTS) and in patients given the diagnosis of clinical Cowden Syndrome (CS). These findings have significant clinical implications, including providing the rationale for testing patients meeting clinical criteria for PHTS/CS with concurrent DNA and RNA testing. It also supports reevaluation of patients who test negative by DNA testing alone but with a clinical diagnosis of PHTS/CS with subsequent RNA testing to identify and clinically interpret previously undetected deep intronic PTEN variants. Where cancer treatment and prevention decisions hinge on correct diagnoses, concurrent DNA and RNA testing rather than stepwise testing can permit faster, more accurate results and earlier clinical actionability.